TINDAK PIDANA PEMERKOSAAN TERHADAP SEORANG WANITA DALAM KEADAAN TIDAK BERDAYA - Yusuf Wibisono; Heru Susetyo Nuswanto (Faculty of Law, Universitas Trisakti, 2023)
The rising incidence of rape has captured public attention, presenting challenges in investigation, prosecution, and verdicts. Rape is defined as a violent act or threat of violence to coerce non-consensual sex with a woman, not one's spouse, exemplified in Decision Number 390/Pid.B/2021/PN Smn. This research delves into the theoretical and regulatory aspects of rape in Indonesia, particularly the application of Article 285 of the Criminal Code to helpless victims, posing questions about its appropriateness. Utilizing a normative approach with descriptive analysis, secondary data was collected through a literature review. The research concluded that the perpetrator's actions constitute 'exploitation rape,' and the victim qualifies as a 'pure victim' with no prior association with the offender. Furthermore, the perpetrator's actions more closely align with the elements of Article 286 of the Criminal Code.